The Influence of Training on the Performance of Food & Beverage Service Department Employees at Four Seasons Resort Bali At Sayan - Winarsa, Ni Putu Bintang Pertiwi; Sadjuni, Ni Luh Gde Sri; Sulistyawati, Ni Luh Ketut Sri (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2024)
Declining employee performance can cause problems for the company. Declining guest comments can indicate a decline in performance, which can affect the hotel's reputation. Developing employee competencies and skills to improve company operations that lead to improved performance. The study was conducted with the intention of determining the effect of training on the performance of food and beverage service employees at the Four Seasons Resort Bali at Sayan Hotel. The data collection methodology was carried out by distributing questionnaires to 38 respondents. The methodology used was the classical assumption test, unit regression analysis, T-test and determination coefficient test using SPSS version 25 for Windows. Based on the analysis, training has a good and significant effect on employee performance (tcount> ttable = 9.279> 2.028). Training has a contribution to influencing employee performance by 70.5% in the strong category.